PEMETAAN TINGKAT ANCAMAN BENCANA BANJIR DI KECAMATAN BATAHAN KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - Lubis, Wahyu Hidayat; Prarikeslan, w (JURNAL BUANA, 2024)
This study aims (1) To determine the level of flood threat in Batahan District (2) To map the distribution of areas that have a flood disaster threat level in Batahan District. The research method used is quantitative descriptive research. Data collection techniques in this study are by means of observation, interviews and literature studies. The data analysis techniques used are scoring and matrix analysis, the results of the study are (1) The threat level of flood disasters in Batahan District is divided into 3 classes, namely High threat class, Medium threat class and Low threat class. (2) The distribution of a low flood threat level of 15.95% or an area of 3399.74 ha spread across 9 villages in Batahan District. The moderate flood threat level is 68.05% or an area of 14828.42 ha spread across 17 villages of Batahan District. The flood threat level is high at 16.05% or an area of 3380.09 ha spread across 10 villages in Batahan District.